133k views
3 votes
4x+3/2x-1+3x-8/x-2=5

2 Answers

7 votes

Answer:

x = 7

Explanation:

I'm assuming you mean:


(4x+3)/(2x-1) +(3x-8)/(x-2)=5

So everything needs to be multiplied by both (2x-1) and (x-2)

(4x+3)(x-2) + (3x-8)(2x-1) = 5(2x-1)(x-2), now you need to FOIL or distribute

4x²-8x+3x-6 + 6x²-3x-16x+8 = 5(2x²-4x-x+2)

4x²-5x-6 + 6x²-19x+9 = 10x²-25x+10, combine like terms

10x²-24x+3 = 10x²-25x+10 put variable on one side and constant on the other

x = 7

User Enticedwanderer
by
4.4k points
6 votes

Answer:

4×+2×+3×3-1-8-2=2

9×-6=5

9×=5-6

9×=-1

9×=-1

9×/9=-1/9

×=-1/9

User Gustavo Morales
by
5.0k points